The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jcm11206053
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT Evaluation of Different Root Canal Irrigation Protocols on the Removal of Accumulated Hard Tissue Debris: A Systematic Review and Meta-Analysis

Abstract: Accumulated hard tissue debris (AHTD) is an inevitable by-product during endodontic treatment and is difficult to remove completely using traditional syringe and needle irrigation (SNI). Adjunctive irrigation is proposed to assist the clean-up of AHTD. This systematic review and meta-analysis aimed to evaluate the AHTD removal efficacy of different root canal irrigation devices using micro-computed tomography (Micro-CT). A literature search was carried out within the main scientific databases until 20 June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…Various methods, such as the canal staining and clearing technique, spiral computed tomography (CT) thin-layer scanning, micro-CT, radiographic examination, cone-beam CT (CBCT), and dental operating microscope, have been employed for evaluating the root canal morphology [ 3 , 7 11 ]. CBCT has been used to assess the root canal morphology owing to its short exposure time, low cost compared to that of conventional CT, high resolution and accuracy, minimal distortion, three-dimensional visualization, and noninvasiveness [ 1 , 5 , 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods, such as the canal staining and clearing technique, spiral computed tomography (CT) thin-layer scanning, micro-CT, radiographic examination, cone-beam CT (CBCT), and dental operating microscope, have been employed for evaluating the root canal morphology [ 3 , 7 11 ]. CBCT has been used to assess the root canal morphology owing to its short exposure time, low cost compared to that of conventional CT, high resolution and accuracy, minimal distortion, three-dimensional visualization, and noninvasiveness [ 1 , 5 , 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that conventional irrigation, without using agitation methods, has low diffusion potential through the root canal system [13,14], leading to endodontic therapy failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laser activated irrigation (LAI) became more popular in endodontic irrigation protocols and the benefits in terms of hard tissue and smear layer removal is evident (Liang et al., 2022). According to current systematic review, LAI is claimed to perform superior compared to ultrasonic activated irrigation in terms of removing microorganisms, dentine debris and smear layer from the root canal system (Badami et al., 2023).…”
Section: Introductionmentioning
confidence: 99%